Hydrogeology and water-dowsing: countercurrents and confluences - Durand, Jean-Yves (2003)
The history of hydrogeology has been well documented by historians of science and technology. Folk conceptions on groundwater have been studied by anthropologists, who have also payed some attention to water-dowsing. However, these bodies of research generally lack an attempt at a joint analysis that would try to bridge the gap between considerations on scientific and non-scientific knoweldges. Trying to do so helps to shed some light on historical exchanges and communications between different means for groundwater detection. Recent ethnographic research in southern Europe shows, for instance, a surge of interest toward water-dowsing on the part of certain professional hydrogeologists (sometimes organized in associations) in spite of its lacking any scientific demonstration for its claims. This example also provides a way to relate such relatively circumscribed cultural shifts to socially much wider current changes in folk representations about water, fostering their better understanding by social sciences.